1997
DOI: 10.1021/jp9626428
|View full text |Cite
|
Sign up to set email alerts
|

Styrene Clusters in a Supersonic Jet:  Reactive and Nonreactive Systems

Abstract: Clusters of styrene with several atoms and small molecules were prepared and studied in a supersonic jet by laser-induced fluorescence (LIF) from S1 and resonance-enhanced multiphoton ionization (REMPI) using S1 as the resonant intermediate state. The dissociation limit can be determined in many cases (e.g., for argon, CO2, and ammonia) by recording the excess energy at which fluorescence from the cluster disappears and styrene fluorescence appears. Parent ion signals are easily observable from clusters excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…The observed blue shift matches well observations for other CO 2 clusters of benzene derivatives. For example, the phenol−CO 2 cluster has its origin displaced by +38 cm −1 , and in the case of styrene, a shift of +51 cm −1 is observed . Similarly, we find that the spectrum detected at m / e = 184 (Figure c) is also reminiscent of the p VP spectrum, although now a red shift of −79 cm −1 is observed.…”
Section: Resultssupporting
confidence: 79%
“…The observed blue shift matches well observations for other CO 2 clusters of benzene derivatives. For example, the phenol−CO 2 cluster has its origin displaced by +38 cm −1 , and in the case of styrene, a shift of +51 cm −1 is observed . Similarly, we find that the spectrum detected at m / e = 184 (Figure c) is also reminiscent of the p VP spectrum, although now a red shift of −79 cm −1 is observed.…”
Section: Resultssupporting
confidence: 79%
“…Size Dependence of LE and CT Emission. The detailed energy requirements for the different processes could not be established for this system (in contrast with others , ), as the excitation spectra are devoid of vibrational structure. The congested character of the spectrum (recall that the systems are jet-cooled) is most probably due to overlap between slightly different absorption spectra due to several clusters differing in size and structure.…”
Section: Discussionmentioning
confidence: 89%
“…The experimental setup is a modification of the setup described in ref . The vacuum chamber consisted of a 6 in.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to benzene, few studies of clusters containing styrene have been reported. , Clusters of styrene with Ar, N 2 , CO 2 , NH 3 , and trimethylamine were studied by laser-induced fluorescence (LIF) and REMPI. , The origin bands of these clusters are shifted by −31, −25.5, +51, +52, and −24 cm -1 relative to the band of the bare styrene molecule. The spectra of the styrene−TMA 1:1 cluster were assigned to two isomeric forms, both capable of forming a charge-transfer complex upon excitation to the locally excited state. , We recently reported the REMPI spectra of styrene (water) n clusters, SW n , with n = 1−2, which indicate that the origin of the SW complex is blue shifted by −22 cm -1 relative to the band of the bare styrene molecule …”
Section: Resultsmentioning
confidence: 99%